Pengelolaan Limbah Hasil Panen Menjadi Pupuk Cair Yang Bernilai Tinggi - Pardosi, Ivan Agustinus; Marasatrio, Habib; Hidayat, Rio Arisman; Illahi, Dellan Illahi; Fringky, Fringky; Meisya, Hilda; Nur’aini, Hesti; Fariadi, Herri (Universitas Dehasen Bengkulu, 2025)
Desa Mekar Sari is an area where the majority of the population works as vegetable and coffee farmers. The village community shows low awareness in managing post-harvest waste, especially organic waste. In order to address this issue, a community service program was implemented to process organic waste into liquid fertilizer. This processing involves the utilization of waste such as banana stems, vegetables, and eggshells mixed with EM4 microorganisms and fermented for 1 to 3 weeks. This program is designed based on survey results and socialization with the community, and aims to improve soil fertility and reduce fertilizer costs for local farmers. The results of this organic liquid fertilizer not only have a positive impact on soil fertility and crop yields but also help reduce the use of chemical fertilizers that could potentially harm the environment. Organic liquid fertilizer has proven to provide economic and environmental benefits for the community of Mekar Sari Village, making this program a sustainable solution in addressing waste issues and improving farmers' welfare.